Biomechanical adaptations in subjects after anterior cruciate ligament reconstruction: Preventing secondary injury - Hoshiba, T.; Fukubayashi, T. (Sports injuries and prevention, 2015)
A secondary anterior cruciate ligament (ACL) injury in a surgically reconstructed limb is of critical concern after ACL reconstruction. Although risk factors for a secondary ACL injury have been recently identified, the risk factors actually caused by ACL reconstruction and their associated behavioral characteristics remain unclear. In this chapter I introduce methods for evaluating biomechanical adaptations during dynamic exercises and summarize current concepts for preventing secondary ACL injury after reconstruction. In earlier studies, the altered loading strategy and joint movement patterns of the reconstructed limb on landing during dynamic exercises were present; thus, to prevent secondary ACL injury, the altered biomechanical function needs to be addressed and eliminated before subjects return to sports participation.